IMPLEMENTATION OF PRIMARY HEALTH CARE SYSTEM IN COUNTRIES - Lukito, Memo; Gani, Ascobat (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: Primary Health Care (PHC) systems are essential for delivering comprehensive and accessible health services globally, focusing on individuals’ and communities’ fundamental health and well-being. Aims: To assess PHC systems to ensure universal access, regardless of socio-economic status or location, by providing comprehensive services such as illness prevention, treatment, rehabilitation, support, and health promotion. Methods: This study utilised the PICO framework, with methods and results of this systematic review based on PRISMA guidelines. Articles were identified through an initial generic search in PubMed, ScienceDirect, and Scopus databases. Results: After the assessment, a total of 18 articles were selected. The following priorities for PHC policy implementation emerged: enhancing collaboration between public and private sectors, improving information sharing through technology and health literacy, establishing quality evaluation systems, and promoting community-based training programs. Identified challenges include workforce shortages, particularly in rural areas, and inadequate coordination between primary and secondary care. Addressing these challenges and focusing on these priorities can lead to better health outcomes and more effective PHC systems. Conclusion: The Alma-Ata Declaration of 1978 was a transformative milestone in global health. It advocated for "Health for All" through Primary Health Care (PHC). Despite initial challenges, the principles of Alma-Ata have significantly influenced PHC systems worldwide. Keywords: Country-specific health primary care, health care systems, primary healthcare